2009
DOI: 10.11646/zootaxa.2158.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and nomenclatural notes on freshwater Gastrotricha

Abstract: Some taxonomic and nomenclatural remarks concerning freshwater species of Gastrotricha Chaetonotida are presented. In the family Chaetonotidae, the subgenus Chaetonotus (Hystricochaetonotus) is synonimized with the subgenus C. (Chaetonotus sensu stricto). The genus Lepidochaetus is moved to a subgeneric rank into the genus Chaetonotus, and the subgenus Nudichaetonotus Schwank, 1990 is synonymized with C. (Lepidochaetus). Chaetonotus (Lepidochaetus) brasilianus is proposed as a replacement name for Chaetonotus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 0 publications
0
40
0
4
Order By: Relevance
“…Given the included data, none of the currently recognized subgenera appear monophyletic except for Chaetonotus (Zonochaeta). Lepidochaetus, considered a subgenus within Chaetonotus by Balsamo et al (2009), is also monophyletic. The hypothesized reinvasion of certain Chaetonotidae (Halichaetonotus and marine Heterolepidoderma in a sister group relation to the freshwater taxon Chaetonotus schultzei Metschnikoff, 1865) from a limnic environment to a marine environment by Kånneby et al (2013) also gains high support in this study (pp=0.98) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the included data, none of the currently recognized subgenera appear monophyletic except for Chaetonotus (Zonochaeta). Lepidochaetus, considered a subgenus within Chaetonotus by Balsamo et al (2009), is also monophyletic. The hypothesized reinvasion of certain Chaetonotidae (Halichaetonotus and marine Heterolepidoderma in a sister group relation to the freshwater taxon Chaetonotus schultzei Metschnikoff, 1865) from a limnic environment to a marine environment by Kånneby et al (2013) also gains high support in this study (pp=0.98) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrotricha is a small phylum of aquatic acoelomate animals with approximately 850 species (see Balsamo et al 2009Balsamo et al , 2013Balsamo et al , 2014Hummon and Todaro 2010;Kieneke and Schmidt-Rhaesa 2014;Todaro et al 2014; and references therein). The group is a common component of the meiofauna and is hypothesized to act as an important link between the microbial loop and larger invertebrate predators (Balsamo and Todaro 2002).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the taxonomy of the order Chaetonotida has been repeatedly revised in the last decades and is still unstable especially at the species level (Schwank 1990, Kisielewski 1991, Kisielewski 1997, Kisielewski 1998, Leasi and Todaro 2008, Balsamo et al 2009, Hummon and Todaro 2010, Balsamo et al 2014). Furthermore, a phylogenetic study based on molecular markers found the largest chaetonotidan family, Chaetonotidae, and most of the genera included in it to be non-monophyletic (Kånneby et al 2013).…”
Section: General Descriptionmentioning
confidence: 99%
“…Kisielewski (1991) provisionally kept Anacanthoderma as a taxon affiliated to Dasydytidae but discusses a systematic position not strictly related to this group. In their recent taxonomic checklist of valid freshwater Gastrotricha, Balsamo et al (2009) class Anacanthoderma among the Dasydytidae (see also Todaro 2012). The results of our analysis yield support for such a classification.…”
Section: Systematic and Evolutionary Aspectsmentioning
confidence: 99%
“…Furthermore, the study also revealed severe differences between the two species such as a differing number of segments of the longitudinal muscles and oblique muscle pairs or an alternative shape of the oblique components, for example thin muscle strands in S. tongiorgii but massive muscle blocks in S. scirtetica (Kieneke et al 2008a). The limited number of species examined from this clade (containing 7 genera; Balsamo et al 2009) makes evolutionary inference, for example a reconstruction of ancestral character states, highly speculative.…”
Section: Introductionmentioning
confidence: 95%